Transformation of the Distribution of the Sedulur Sikep Samin Community, Blora Regency - Achmad Nur Hidayaht; Budiaman Budiaman; Nandi Kurniawan (Journal of Geography Science and Education, 2022)
The Transformation of the Distribution of the Sedulur Sikep Samin Community, Blora Regency Abstract The Samin community is a community that emerged in the Dutch colonial era, this community is part of Javanese society which teaches about equality in life and freedom to practice their beliefs (manunggaling kawulo gusti), the Samin community has procedures, customs, languages , and norms and has a unique history, in its emergence can not be separated from the arrival of the Dutch colonial government which implemented forced cultivation and land taxes for the natives which was the background for the emergence of teachings from the Samin community. The emergence of the samin movement or better known as geger samin is the movement of samin surosentiko or raden kohar who is believed to have one lineage with the king of Majapahit. This samin movement strengthened in 1890 in Blora Regency, then expanded to various areas in Blora Regency including Sambong, Doplang, Randublatung, Kedungtuban, and shared other districts such as Rembang Regency, Pati Regency, Grobogan Regency, and Bojonegoro Regency. This study focuses on describing the transformation of the distribution of the Samin community in Blora Regency with a local knowledge approach (emic) with a field survey method to find out the location and map the distribution of the Samin community that still exists in maintaining their culture.